Stair Gait in Older Adults Worsens With Smaller Step Treads and When Transitioning Between Level and Stair Walking - Di Giulio, Irene; Reeves, Neil D.; Roys, Mike; Buckley, John G.; Jones, David A.; Gavin, James P.; Baltzopoulos, Vasilios; Maganaris, Constantinos N. (Frontiers in Sports and Active Living, 2020)
Older people have an increased risk of falling during locomotion, with falls on stairs being particularly common and dangerous. Step going (i.e., the horizontal distance between two consecutive step edges) defines the base of support available for foot placement on stairs, as with smaller going, the user's ability to balance on the steps may become problematic. Here we quantified how stair negotiation in older participants changes between four goings (175, 225, 275, and 325 mm) and compared stair negotiation with and without a walking approach. Twenty-one younger (29 ± 6 years) and 20 older (74 ± 4 years) participants negotiated a 7-step experimental stair. Motion capture and step-embedded force platform data were collected. Handrail use was also monitored. From the motion capture data, body velocity, trunk orientation, foot clearance and foot overhang were quantified. For all participants, as stair going decreased, gait velocity (ascent pA = 0.033, descent pD = 0.003) and horizontal step clearance decreased (pA = 0.001), while trunk rotation (pD = 0.002) and foot overhang increased (pA,D < 0.001). Compared to the younger group, older participants used the handrail more, were slower across all conditions (pA < 0.001, pD = 0.001) and their foot clearance tended to be smaller. With a walking approach, the older group (Group x Start interaction) showed a larger trunk rotation (pA = 0.011, pD = 0.015), and smaller lead foot horizontal (pA = 0.046) and vertical clearances (pD = 0.039) compared to the younger group. A regression analysis to determine the predictors of foot clearance and amount of overhang showed that physical activity was a common predictor for both age groups. In addition, for the older group, medications and fear of falling were found to predict stair performance for most goings, while sway during single-legged standing was the most common predictor for the younger group. Older participants adapted to smaller goings by using the handrails and reducing gait velocity. The predictors of performance suggest that motor and fall risk assessment is complex and multifactorial. The results shown here are consistent with the recommendation that larger going and pausing before negotiating stairs may improve stair safety, especially for older users.